THE IMPLEMENTATION OF INTERNET OF THINGS USING TEST BED IN THE UKMNET ENVIRONMENT - Mohd Zaki Ibrahim; Rosilah Hassan (Asia-Pacific Journal of Information Technology and Multimedia, 2019)
The Internet of Things (IoT) is one of the most important components for the 4.0 industrial revolution. In order to implement IoT within an organization or environment, it requires deep research to ensure that will works properly. Among today's problems of computing is the need for high power consumption and considerable space and equipment usage. Therefore, a small-sized technology and requires only low power to operate is necessary. A study has been conducted to study the implementation of Internet of Things within the UKM network environment known as UKMNet. In order to make this research more realistic, a test bed is developed using an Arduino Uno board as the IoT Hardware. Then a scenario is created by connecting this Arduino Uno board to four sensors to measure temperature, current and voltage. After that, the reading value will be sent to the Arduino Uno board to calculate the amount of power used in watts so that these values are stored to the database server. To test the performance of the connection between the Arduino board and the server, the iPerf software is use. The metrics on performance tests are data rates, jitter and loss of data packets. As a result of this study, we found that Arduino Uno is suitable for use as the IoT hardware for this scenario. Performance tests for Arduino board that are connected to UKMNet meet the requirements for the implementation of IoT where the data transmission rate is between 3.483 Mbps up to 3.563 Mbps. The jitter value for this connection is also lower than 1.80 milliseconds to 1.85 milliseconds while the packet loss rate recorded is 0% to 0.59% for 10 seconds of data transmission. In conclusion, IoT by using Arduino Uno as an IoT hardware is suitable to implement in the UKMNet environment.